Early repeat computed tomographic imaging in transferred trauma and neurosurgical patients: Incidence, indications and impact. Issue 4 (5th February 2018) - Blazak, Penni; Hacking, Craig; Presneill, Jeffrey; Reade, Michael
Abstract: Introduction: Computed tomographic (CT) imaging is widely available in Australian rural and remote hospitals and is often performed prior to patient transfer to definitive tertiary hospital care. We hypothesised that critically ill trauma and neurosurgical patients might have CT scans repeated after interhospital transfer and that the utility of this practice might be low in relation to the additional financial cost and radiation exposure. Methods: We conducted a retrospective review of clinical records to determine the proportion of trauma and neurosurgical patients transferred to our tertiary ICU from other hospitals between 1 June 2013 and 30 June 2014 who underwent a repeat CT scan. The additional effective radiation dose was estimated using the dose length product method and the Australian Medicare Benefits Schedule was used to estimate the associated cost. Results: Of the 247 patients transferred for trauma and neurosurgical indications, many (144; 58%) had undergone CT imaging at the referring hospital. Repeat scans were performed in 60 (42%) already imaged patients (24% of all transferred patients), most frequently for changed clinical indications. While in 11 (18%) of those 60 already imaged patients the repeat scan led to an identifiable change in management, for another 13 (22%) patients the repeat scans appeared to be potentially avoidable. The median cost of a repeat scan was AU$250 and the median additional effective radiation dose was 2.74 mSv per patient. Conclusion: Repeat CT scans for patients already imaged prior to transfer were relatively common, occurring mostly for apparently valid clinical reasons. However, the additional radiation risk and financial cost of these repeat scans appeared on retrospective audit to be potentially avoidable in approximately one in five cases.